2013
DOI: 10.1002/mds.25736
|View full text |Cite
|
Sign up to set email alerts
|

Progression of intestinal permeability changes and alpha‐synuclein expression in a mouse model of Parkinson's disease

Abstract: Parkinson’s disease (PD) is a multifocal degenerative disorder for which there is no cure. The majority of cases are sporadic with unknown etiology. Recent data indicate that untreated patients with de novo PD have increased colonic permeability and that both de novo and premotor patients have pathological expression of α-synuclein (α-syn) in their colon. Both endpoints potentially can serve as disease biomarkers and even may initiate PD events through gut-derived, lipopolysaccharide (LPS)-induced neuronal inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 226 publications
(208 citation statements)
references
References 64 publications
6
190
1
4
Order By: Relevance
“…A recent report that individuals with PD have increased intestinal permeability suggests another mechanism, in addition to infection, that might provoke the expression (or accumulation) of αS within the ENS 25,26 , namely the exposure of the ENS to commensal microbes. In another study, orally administered E. coli producing curli protein, a protein that facilitates bacterial attachment to epithelial cells and subsequent invasion, enhanced αS deposition in plexi in the gut and in hippocampus and striatum in aged Fischer 344 rats (which spontaneously accumulate αS within their ENS as they age 27 ) as compared to rats exposed to mutant bacteria lacking the capacity to produce curli or to rats exposed to vehicle 3 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent report that individuals with PD have increased intestinal permeability suggests another mechanism, in addition to infection, that might provoke the expression (or accumulation) of αS within the ENS 25,26 , namely the exposure of the ENS to commensal microbes. In another study, orally administered E. coli producing curli protein, a protein that facilitates bacterial attachment to epithelial cells and subsequent invasion, enhanced αS deposition in plexi in the gut and in hippocampus and striatum in aged Fischer 344 rats (which spontaneously accumulate αS within their ENS as they age 27 ) as compared to rats exposed to mutant bacteria lacking the capacity to produce curli or to rats exposed to vehicle 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms like constipation, dysbiosis, altered intestinal permeability and enteric accumulation of a-synuclein co-exist with the inflammation in the GI tract. [72][73][74][75] Persistant inflammation in the gut leads to systemic inflammation and ultimately neuroinflammation. Recent studies have reported that gut inflammation and oxidative stress do exist in patients with PD.…”
Section: Identifying Reliable Early Non-motor Biomarkersmentioning
confidence: 99%
“…The GI inflammation is associated with symptoms like constipation, intestinal permeability, dysbiosis, and higher levels of pathogenic enteric a-synuclein (together characterized as GI dysfunction) that appear more than two decades before the onset of motor symptoms. [72][73][74][75] Also, studies have reported that PD patients show inflammation and oxidative stress in the gut.…”
Section: 101mentioning
confidence: 99%
“…Characteristic deposition of α-synuclein in human PD patients [51] and altered patterns of phospho-α-synuclein aggregates [52] as well as elevated total intestinal permeability [53] have been reported. Together with the fact that SNP within peptidoglycan-recognizing protein genes are associated with PD [54] and that systemic application of LPS leads to an immediate and progressive increase in α-synuclein expression in the large intestine of mice [55], the gut itself might have the potential to contribute to disease progression in PD rather than merely reflecting pathology in a non-CNS organ.…”
Section: Impact Of Gut Microbiota On Neurodegenerative Diseasesmentioning
confidence: 99%